2013
DOI: 10.1016/j.ccr.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p53 in Enterocytes Generates an Inflammatory Microenvironment Enabling Invasion and Lymph Node Metastasis of Carcinogen-Induced Colorectal Tumors

Abstract: Loss of p53 is considered to allow progression of colorectal tumors from the adenoma to the carcinoma stage. Using mice with an intestinal epithelial cell (IEC)-specific p53 deletion, we demonstrate that loss of p53 alone is insufficient to initiate intestinal tumorigenesis but markedly enhances carcinogen-induced tumor incidence and leads to invasive cancer and lymph node metastasis. Whereas p53 controls DNA damage and IEC survival during the initiation stage, loss of p53 during tumor progression is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
231
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(252 citation statements)
references
References 45 publications
18
231
1
2
Order By: Relevance
“…135 Loss of p53 induced the EMT-activating transcription factor Twist and the accumulation of myeloid cells, which in turn produced proinflammatory factors (such as CXCL1, CXCL2, CCL2 and COX2) capable of paracrine STAT3 activation in tumor cells. 135 Inflammationmediated NF-kB activation also induces EMTand metastasis in breast cancer. 40,136 The activation of oncogenes leading to inflammation that triggers the NF-kB pathway has also been described.…”
Section: Molecular Pathways Of Metastasis-promoting Inflammationmentioning
confidence: 99%
“…135 Loss of p53 induced the EMT-activating transcription factor Twist and the accumulation of myeloid cells, which in turn produced proinflammatory factors (such as CXCL1, CXCL2, CCL2 and COX2) capable of paracrine STAT3 activation in tumor cells. 135 Inflammationmediated NF-kB activation also induces EMTand metastasis in breast cancer. 40,136 The activation of oncogenes leading to inflammation that triggers the NF-kB pathway has also been described.…”
Section: Molecular Pathways Of Metastasis-promoting Inflammationmentioning
confidence: 99%
“…The early response to AOM is altered in Naip1-6 / mice AOM induces O-6 methylguanine adducts on DNA guanine, causing G-to-A base changes, which usually elicits a wave of p53-mediated apoptosis that can be detected early after AOM injection (Hu et al, 2002;Kerr et al, 2013;Schwitalla et al, 2013). Failure to repair damaged DNA, or to eliminate AOMmutated cells, leads to increased tumor burden (Schwitalla et al, were all increased in Naip1-6 / mice (Fig.…”
mentioning
confidence: 99%
“…This lack of correlation between tumorigenesis and inflammation led us to check whether Naip1-6 deficiency could also lead to increased tumorigenesis in an inflammation-independent setting. To test this, we used a model of AOM-induced CRC that is free of DSS or other inflammatory challenges (Schwitalla et al, 2013). Mice were injected with AOM (10 mg/kg) once per week for 6 wk and were assessed for tumor burden after 24 wk.…”
mentioning
confidence: 99%
“…It can interact with p53 and the homeodomain-interacting proteinkinase-2 within the promyelocytic leukemia nuclear bodies, modulating p53 transcriptional activity (Tomasini et al, 2003). Loss of p53 during tumor progression is associated with increased intestinal permeability, causing formation of an NF-κB-dependent inflammatory microenvironment and the induction of EMT (Schwitalla et al, 2013). It was revealed that miR29a was up regulated in mesenchyme, metastatic RasXT cells relative to epithelial EpRas cells, and could suppress the expression of tristetraprolin, a protein involved in the degradation of messenger RNAs with AU-rich 3'-untranslated regions, and led to EMT and metastasis in cooperation with oncogenic Ras signaling (Gebeshuber et al, 2009).…”
Section: Discussionmentioning
confidence: 99%